The Impact of Environmental Crisis on Sustainable Tourism Development: A Study on Kuakata - Mia, Md Nasir (Dhaka University Journal of Business Studies, 2026)
Tourism has become a fashionable leisure activity throughout the world. It generates revenue for the destination countries and creates more employment avenues for the community. Tourism is a growing industry in Bangladesh. The country is blessed with thousands of tourist spots. Cox's Bazar is the longest sea beach in the world. Kuakata Sea Beach has ranked second in terms of length. The beach is situated in the southern part of Bangladesh. The virgin beach is beset with many attractive sites. The research aims to determine the impact of the environmental crisis on sustainable tourism development in Kuakata. Data were collected in two ways to reach the research goal. First, literature was reviewed to identify issues related to environmental crises and sustainable tourism development; thus, ten (10) cases were identified in this connection. Second, interviews were conducted using a closed-ended questionnaire to identify the environmental crisis affecting sustainable tourism development at Kuakata. This survey shows that Kuakata is beset with various problems (natural hazards and man-made disasters) such as coastal erosion, water pollution, floods, tide surges, excessive rain, earthquakes and deforestation, insufficient tourism infrastructure and superstructure, waste and sewage disposal, tourist inflow beyond the carrying capacity, lack of awareness about conservation and development of tourism facilities, absence of a proper monitoring system of tourism assets, absence of policy supports engaging the local community in tourism activities, lack of planning for mitigation of environmental crises, poor management by tourism authorities, etc. After that, a Prioritization Matrix (PM) has been prepared to show the significance and extent of their impacts on the Kuakata seashore. To mitigate the environmental crisis, some SMART (Specific, Measurable, Attainable, Realistic, and Time-Bound) objectives are set based on the findings of the prioritization matrix. Lastly, a short and long-term action plan has been created to take the necessary steps for sustainable tourism development in Kuakata. Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 187-210